Department of Periodontology and Oral Medicine, Hospital of Dentistry, Anhui Medical University, Hefei, China - ahmed, yaser; ALAQILI , SAMAR (MDS); YUAN , WANG (Professor) (IJRDO -JOURNAL OF HEALTH SCIENCES AND NURSING, 2021)
Giant granular cell tumour of the adult female is an uncommon benign tumour of uncertain origin. The typical clinical appearance is of a single nodule occurring on the left posterior maxillary area . In 10% of cases there are multiple lesions. The occurrence of Giant granular cell tumour in Chinese is rare.Case situation  : One firm pedunculated nodular lesions were noticed ( mass ) in the mouth of a 25-old Chinese female: one on the left posterior maxillary moler +8 area.Conclusion: Surgical wound healing using electrocautery is faster compared to other techniques, chance giant cell tumor recurrence and Giant granular cell tumour occurs almost exclusively in Chinese newborns but also rarely in adult female. The Patient should be assured of the benign nature and the simple treatment of the condition.Giant granular cell tumour occurs almost exclusively in Chinese newborns but also rarely in adult female.